$$(3 \times 10^{-1}) \times (3 \times 10^{-1}) =$$

Incorrect.
[[snippet]]

Incorrect.
[[snippet]]

Correct.
[[snippet]]
>$$(3 \times 10^{-1}) \times (3 \times 10^{-1}) = (3 \times 10^{-1})^2$$
Split the power to individual bases, creating a power in scientific form.
>$$ (3 \times 10^{-1})^2=3^2 \times 10^{-2}$$
>$$3^2 \times 10^{-2}=9 \times 10^{-2}$$
Since the 10 part has an exponent of -2, shift the decimal point **two** places to the **left**.
>$$9 \times 10^{-2}=0.09$$

Incorrect.
[[snippet]]

Incorrect.
[[snippet]]

$$0.001$$

$$0.009$$

$$0.09$$

$$0.1$$

$$0.9$$